DETEKSI DINI KECEMASAN PADA ASUHAN KEBIDANAN MASA KEHAMILAN, PERSALINAN DAN MASA NIFAS NY. A G2P1A0 DI KLINIK “A” KABUPATEN BANDUNG - Eka Alia Agustina; Dyeri Susanti; Damai Yanti; Yosi Oktri (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2026)
Pregnancy involves normal physiological changes that are often accompanied by psychological responses, one of which is anxiety, particularly during the third trimester. Unmanaged anxiety, combined with limited support from the husband or family, may negatively affect maternal and fetal health, the childbirth process, and the postpartum period. This study aimed to identify anxiety early and implement appropriate midwifery interventions to prevent potential complications. A descriptive case study with an observational approach was conducted on Mrs. “A” (G2P1A0), starting at 36 weeks of gestation and continuing through labor, the postpartum period, newborn care, and contraceptive counseling. Anxiety levels were assessed using the Taylor Manifest Anxiety Scale (T-MAS). Midwifery interventions included health education, counseling, therapeutic communication, prenatal yoga exercises, and breathing relaxation techniques. Prior to the intervention, the T-MAS score indicated moderate anxiety, mainly influenced by limited spousal presence and insufficient family support. Anxiety increased during labor due to the indication for cesarean section, and during the postpartum period due to family pressure related to infant feeding practices. After structured and continuous interventions, anxiety levels decreased to a mild category. The pregnancy, delivery, and postpartum period proceeded without complications. These findings indicate that early psychological screening combined with holistic midwifery care is effective in reducing anxiety and supporting maternal and neonatal well-being.